Cancer incidence among Icelandic deck officers in a population-based study - Sulem, Patrick; Rafnsson, Vilhjálmur (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'The aim of this study was to define the cancer pattern in an Icelandic cohort of deck officers while indirectly controlling for their smoking habits. ' ' METHODS ': 'A cohort of 3874 male deck officers was followed from 1966 to 1998. It was record-linked by the deck officers` personal identification numbers to population-based registers containing each person`s vital and emigration status and cancer diagnosis. Standardized incidence ratios (SIR) were calculated for all cancers and different cancer sites in relation to different lag times and years of birth. Information on smoking habits was obtained by from a questionnaire administered to a sample of the cohort (N=728). ' ' RESULTS ': 'In the total cohort 436 cancers were observed, equal to the expected 436 [SIR 1.0, 95% confidence interval (95% CI) 0.9-1.1], and a significantly increased risk of soft-tissue sarcoma (SIR 2.7, 95% CI 1.2-5.1) was found together with a decreased risk of testis cancer (SIR 0.0, 95% CI ·· -0.7) and urinary bladder cancer (SIR 0.5, 95% CI 0.3-0.8). The deck officers` smoking habits were similar to those found in a sample of the general population. The predictive value was 1.11 for lung cancer and 1.04 for bladder cancer. ' ' CONCLUSIONS ': 'An increased incidence of soft-tissue sarcoma was found among deck officers. This increase resembles that previously found for Swedish deck officers, and it warrants further study.
Keywords: bladder neoplasm; cancer incidence; deck officer; electromagnetic fields; Iceland; population-based study; smoking; soft tissue sarcoma; testis neoplasm